Seed pre-treatment strategy effect on the emergence and vegetative yield of fluted pumpkin (Telfairia occidentalis (F.) Hook) - Effa, Emmanuel B.; Elemi, Ekama D.; Uwak, Glory E.; Uko, Aniefiok E.; Iren, Otobong B. (Journal Of Agriculture, Forestry & Environment, 2025)
A field experiment was conducted at the Teaching and Research Farm, University of Calabar, Calabar during the early cropping season of April – September, 2017 and 2018 to investigate the effects of seed pretreatment strategies on emergence and vegetative yield of fluted pumpkin. The study was arranged in Randomized Complete Block Design (RCBD) with three replications. Treatments included five levels of shed drying (in days) – 1, 2, 4, 6 and the control in which seeds were sown as soon as extracted from the pods. Data were collected on percentage germination, vine length (cm), number of leaves per plant, number of regrowth, leaf area (cm2) as well as fresh and dry weight of shoots. Data were subjected to analyses of variance (ANOVA) procedure and significant means compared using Fishers’ Least Significant Difference at 5 % probability level. Results revealed that drying fluted pumpkin seeds under shed for 4 days prior to sowing enhanced germination percentage (85.20 and 90.00 %), vine length, regrowth (robust development of lateral branches) as well as shoot weight (2.59 t/ha), leaf fresh weight (3.18 t/ha) in 2017 and leaf fresh weigh (3.42 t/ha) in 2018. Drying seeds of fluted pumpkin for four days is hereby recommended for adoption by farmers for optimum yield in Calabar and its environs.